Study of the Problems of Minor Irrigation - Planning Commission (Planning Commission, 1961)
Throughout the history of India, small irrigation works have been the backbone of agriculture in most parts of the country. Over the last 100 years or so, however, the efforts of the Government in the country have largely been directed to extension of irrigation through works of the larger type and, in particular, those involving diversion of river waters for distribution through canals. Even so, the Indian Irrigation Commission (1901-03), the report of which still remains the most comprehensive and exhaustive inquiry of the position in regard to irrigation in India, gave considerable attention to the smaller irrigation works, and in particular, suggested a scheme of their classification which has been followed ever since.
Programme Evaluation Organisation Planning Commission Government of India